Modelling of spray-wall impingement - Rodrigues, Christian Michel Gomes (2016)
When a drop collides with an interposed surface, three phases are usually involved: liquid (the drop), solid (the substrate) and gas (the surrounding environment). Such an event involves a number of parameters associated with the physical characteristics of the incident particles, the properties of the target surface, and the natural features of the air flow. Each occurrence leads to a singular outcome, since each particle experiences a different reality throughout the injection cycle. Therefore, the development of appropriate modelling strategies of this complex multi-phase flow requires a thorough understanding of the mechanisms underlying the spray impingement process. Several computational models have been reported in the open literature, although not always successfully. From these, only a few have attempted to replicate the more intricate scenarios that include the formation and development of a liquid film over the surface due to the deposition of previously injected particles, the presence of a high velocity cross-flowing gas, and the thermal effects promoted by the existence of hot walls. Even though these elements are some of the more influential parameters affecting the final outcome of spray-wall impacts, most of the simulations still neglect some of them in their formulation. Therefore, in order to capture the majority of the physical phenomena observed in experimental studies, CFD codes must be equipped with superior mathematical formulations. During the present doctoral research, three independent computational extensions have been devised and integrated into the model used by our research group to simulate spray-wall interactions. The upgrades — that have been proposed over the course of the study — have been denominated as the liquid film, evaporation and breakup sub-models. They are intended to complement the basic mathematical formulation adopted in the original simulation procedure. This approach has contributed to enhance the prediction capabilities of the model, since it is now capable of capturing some phenomena that were not considered previously. On the other hand, it has also extended the range of applicability of the CFD code to a new set of impact conditions (i.e., in hot environments and with a high velocity crossflow). Furthermore, the present work provides a detailed analysis of the results obtained, with major emphasis given to the disintegration mechanisms and secondary droplet characteristics. Both quantitative and qualitative comparisons between computational and experimental results are presented. When pertinent, the impact of a particular sub-model onto the outcome predicted is also evaluated by comparing the versions of the model with and without the corresponding computational extension. Moreover, a systematic approach is adopted at each section to infer the influence of different parameters on the final outcome. This methodology has been decisive to better understand the factors affecting the phenomena occurring during impact.